Correlation Between Sialidase NEU1 mRNA Expression Changes in Autism Spectrum Disorder - Zhang, Haiqing; Gu, Yuhang; He, Wenxiang; Kuo, Fengyi; Zhang, Yiran; Wang, Duan; He, Li; Yang, Ying; Wang, Hepeng; Chen, Yanni (Frontiers in Psychiatry, 2022)
Abnormal alterations in enzymes functioned in sialic acid modifications may be associated with ASD. In order to study the differences in peripheral blood sialidase NEU1 mRNA expression between autism spectrum disorder (ASD) children and healthy control, and to examine the correlation between NEU1 mRNA expression and the main behavioral phenotypes in ASD children, we performed Real-time Quantitative polymerase chain reaction (qPCR) to measure NEU1 mRNA expression in peripheral blood of 42 ASD children and 42 healthy controls. In addition, we used ADOS-2 to measure and evaluate the behavioral phenotypes of ASD children. Our results showed that NEU1 mRNA in the ASD group was significantly higher than the control group (P< 0.0001). In addition, the ADOS-2 diagnostic scores of 42 ASD children were correlated with their NEU1 mRNA expression results (R=0.344, P=0.0257). Moreover, in general, NEU1 mRNA expression was also positively correlated with the Social Affect (SA) of ADOS-2 (R=0.3598, P=0.0193) but not with the Restricted and Repetitive Behavior (RRB) (R=0.15, P =0.3432). Our results indicated that Sialidase NEU1 mRNA was significantly increased in the ASD children, and its expression was correlated with the SA of the ASD children, which suggested that sialidase NEU1 may affect the SA of ASD. Our data highlighted the potential of NEU1 expression change may play an important role in ASD disease and lay the foundation for further studies on the relationship between NEU1 and ASD.